Evaluating the Benefits of Early Intensive Rehabilitation for Patients With Sepsis in the Medical Intensive Care Unit: A Retrospective Study. Issue 4 (13th October 2021) - Uthup, Bahitha R.; Myszenski, Adele; Saigh, Nora; Samuel, Preethy S.
Abstract : Purpose: To evaluate the benefits of early rehabilitation intervention for patients with sepsis in a medical intensive care unit (MICU) and to identify the factors associated with positive outcomes at discharge. Methods: A retrospective review of 97 electronic medical records of patients with sepsis admitted to 2 similar-sized MICU pods of an urban tertiary care hospital was conducted. Bivariate analyses were conducted to compare the sociodemographics, length of stay, mobility level, and discharge disposition of 47 patients who received early rehabilitation intervention in MICU pod 1, with 46 patients who received standard rehabilitation intervention in MICU pod 2. In addition, multivariate analysis of the entire sample was conducted to identify the factors associated with positive discharge outcomes. Results: Patients in pod 1 had significantly higher level of mobility at discharge (mean difference = 0.80, P = .009) and a better discharge disposition (λ 2 = 25.05, df = 7, P < .001) than those in pod 2. The positive outcomes of increased mobility and return to home at discharge were associated with rehabilitation intensity ( F 1, 91 = 52.30; P < .001, b = 0.82) and rehabilitation initiation (adjusted odds ratio: 0.85, P = .039), respectively. Conclusion: These findings provide empirical support for the safety and benefits of providing early intensive rehabilitation for patients in the MICU with sepsis using a therapist-driven model of care.